3DP of bioinspired reinforced composites - Ahmad Ajyaad Abdul Rahim (Nanyang Technological University, 2022)
Direct ink writing is a form of additive manufacturing that is becoming increasingly more popular among manufacturers due to its versatility in mechanical properties and physical geometrical shape. The process uses a ink or slurry and use a 3D printer to fabricate a part. In this paper, the fabrication of bioinspired composites using an epoxy, glass fibres, carbon nanotubes and carbon black reinforcements are studied. This report contains the details of slurry preparation, evaluation of each slurry recipe, and choosing one final test sample. This sample is then evaluated by mechanical testing and micro-structure assessment.